Vertex operator representations of type Cl⁽¹⁾ and product-sum identities - Li-Meng, Xia; Naihong, Hu (Український математичний журнал, 2014)
We construct a class of homogeneous vertex representations of Cl⁽¹⁾, l ≥ 2, and deduce a series of product-sum identities. These identities have fine interpretation in the number theory. Побудовано клас рівномірних вершинних зображень Cl⁽¹⁾, l ≥ 2. Отримано низку тотожностей типу сум i добутків. Ці тотожності мають змістовну інтерпретацію теорії чисел.